The Concept of Literacy Vocational-Based E-Module of Technical Mechanical Subject - Maulana, A; Puspita, A J; Pangastuti, K K; Daryati, D; Arthur, R (Journal of physics. Conference series, 2022)
Vocational literacy is the development of scientific literacy customized to the needs of the SMK level. This can be described as the use of literacy and numeracy to build skills related to their fields. This study aims to explain the concept of Technical Mechanics E-Module based on vocational literacy for SMK level, especially in building engineering. This subject is relevant to improving vocational literacy skills, considering that this subject is a derivative of Physics which is generally used to hone scientific literacy skills at the junior and senior high school levels. The method used is to study literature by identifying and processing the existing research results. The results of this study indicate that the development of the E-Module refers to knowledge, the process towards competence, and work attitudes by paying attention to work preparation, student responses to the latest technology, establishing networks and communication, and collaboration in work. A vocational literacy-based e-module is built based on abilities, problems, and needs that align with the characteristics of SMK Building Students, so it can be used to identify and improve their vocational literacy skills.